The Whispers - Howard, Greg (Gregory Steven) (Puffin Books, 2020)
Eleven-year-old Riley believes in the Whispers, magical wood creatures that will grant you wishes if you leave them tributes. Riley has a lot of wishes. He wishes bullies at school would stop picking on him. He wishes Dylan, his 8th grade crush, liked him, and Riley wishes he would stop wetting the bed. But most of all, Riley wishes for his mom to come back home. She disappeared a few months ago and Riley is determined to find her. So he goes on a camping trip with his friend Gary to look for the Whispers and ask them to bring his mom back home. But Riley doesn't realize the trip will shake the foundation of everything that he believes in for forever.